SUBSTANTIAL CHARACTERISTICS OF THE MODERNIZATION OF THE INTERNAL TRADE SYSTEM - KACHAN, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The evolution of scientific views regarding the study of the essence of modernization is summarized and its periods are highlighted - industrialization and the formation of the initial provisions of the modernization theory, strengthening of industrialization and the approval of the basic provisions of the modernization theory, post-industrialization and the expansion of the provisions of the modernization theory, neo-industrialization and the formation of new approaches to modernization. The concept of modernization should be considered from the standpoint of increasing the efficiency of the country's economic system, when there is a need for qualitative changes in its structure and renewal of all spheres, which not only ensures the stability of achieving goals, but also forms the necessary potential for dynamic growth. It is emphasized that modernization provides system-structural shifts that critically change traditional ways of functioning, provide for their updating and reformatting in order to achieve higher efficiency and effectiveness of use. The components (organizational, economic, financial, innovative, institutional, social) and aspects of the essential interpretation of the concept of "modernization of the internal trade system" are defined. It is proposed to understand the modernization of the internal trade system as an objective change in the quality characteristics of its renewal and modernization, as a result of which a higher level of efficiency and structurally balanced growth is achieved. The modernization of the internal trade system has its own concept and socio-economic differences, which were formed based on the peculiarities of the establishment and development of trade relations. Modernization is synonymous with the processes of modernization, updating, reformatting, etc., but for their qualitative regulation and planning, it is necessary to analyze the relevant consequences, influencing factors, etc.
Keywords: modernization; internal trade; industrialization; society; renewal